Structural anatomy of deep fascia, it’s implication in the pathogenesis of compartment syndrome of upper limbs and objective assessment of the effect of fasciotomy - Agrawal, Neeraj K.; Agrawal, Preeti; Dubepuria, Rahul (International Surgery Journal, 2020)
Background: Deep fascia is dense and well developed in limbs. In the upper limb the deep fascia is tightly adherent to the underlying muscles especially in the forearm, thereby, restricting the space available to muscular swelling causing painful compartment syndrome. Division of this inelastic fascia or fasciotomy is an emergency procedure to decrease the morbidity and mortality. Methods: 30 patients with acute compartment syndrome of the upper extremity of various aetiologies were studied. Adults with painful, swollen and tense upper extremities with progressive neurological dysfunction were studied. Compartment pressures before and after fasciotomy were measured by a standard Whiteside’s device. Various fasciotomies were carried out and associated skeletal and vascular injuries were also noted. Results: The majority of patients were males with average age being 29.33 years. 56.67% patients with upper limb compartment syndrome sustained road traffic injury, 20% were constrictive tight cast, 20% of patients sustained burn and 1 patient was shot by bullet. Of the 30 patients fractures of both ulna and radius (40%) were the most common. Fractures of the humerus, radius, ulna and small bone of metacarpals together account for 36.67% of the affected patients. 3 patients were found to have injury to major vessels. Compartment pressure was measured by Whiteside’s device and fasciotomy resulted in a drastic drop of the pressure from pre-fasciotomy pressure of 44.8±7.9 mmHg to post-fasciotomy pressure of 12.33±3.61 mmHg. Conclusions: The diagnosis of compartment syndrome should be confirmed swiftly and prompt fasciotomy is the treatment of choice. This offers the best chance at decreasing compartment pressure and preventing further damage.